Hubungan Pengetahuan dengan Kejadian Anemia pada Remaja Putri di SMA PGRI 4 Banjarmasin - Atika Ahdiah; Farida Heriyani; Istiana Istiana (Homeostasis, 2018)
Abstract: Anemia is a condition in which the hemoglobin (Hb) level is <12 g/dl. The prevalence of anemia in the world based on World Health Organization (WHO) data ranges from 40-80%. Knowledge about anemia should be known by women, especially female adolescent, so it can be applied in everyday life in order to prevent anemia. This study aims to determine the correlation between knowledge to the incidence of anemia in female adolescent in PGRI 4 High School Banjarmasin. This research method used observational analytic with cross sectional approach. The number of samples were 56 female students who met the inclusion criteria and taken by proportional stratified random sampling. The research instrument was informed concent form sheet, respondent identity data, questionnaire consist of 10 multiple choice questions and pens. The result of the research found that 41.1% of respondents have less knowledge, 44.6% have sufficient knowledge and 14.3% have good knowledge anemia with status anemia are 64,3% and 35,7% not having anemia. The result of statistical test showed a significant correlation between knowledge to the incidence of anemia in female adolescent in PGRI 4 High School Banjarmasin (ρ = 0,037). Keywords: anemia, knowledge, female adolescent  Abstrak: Anemia adalah suatu kondisi dimana kadar hemoglobin (Hb) <12 g/dl.Prevalensi kejadian anemia di dunia berdasarkan data World Health Organisation (WHO) berkisar antara 40-80%. Pengetahuan tentang anemia perlu dimiliki oleh remaja putri dalam upaya pencegahan kejadian anemia. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan dengan kejadian anemia pada remaja putri di SMA PGRI 4 Banjarmasin. Metode penelitian yang digunakan adalah observasional analitik dengan pendekatan cross sectional. Jumlah sampel sebanyak 56 orang siswi yang memenuhi kriteria inklusi dan diambil dengan cara proporsional stratified random sampling. Instrumen penelitian berupa lembar informed concent, data isian identitas responden, lembar kuesioner sebanyak 10 soal pilihan ganda dan alat tulis. Hasil penelitian didapatkan sebanyak 41,1 % responden berpengetahuan kurang, 44,6% berpengetahuan cukup dan 14,3% berpengetahuan baik dengan status anemia sebanyak 64,3% dan tidak anemia 35,7%. Hasil uji statistik didapatkan hubungan yang bermakna antara pengetahuan dengan kejadian anemia pada remaja putri di SMA PGRI 4 Banjarmasin (ρ=0,037). Kata-kata kunci: anemia, pengetahuan, remaja putri